Diagnosing slipped capital femoral epiphysis amongst various medical specialists. (April 2018) - Lam, A.; Boenerjous, S. A.; Lo, Y.; Abzug, J. M.; Kurian, J.; Liszewski, M. C.; Sanderson, D. E.; Scholnick, J. M.; Taragin, B H.; Gomez, J. A.; Otsuka, N. Y.; Hanstein, R.
Purpose: To evaluate sensitivity, specificity and accuracy of a radiographic slipped capital femoral epiphysis (SCFE)-diagnosis among medical specialists. Methods: Three paediatricians, three paediatric radiologists and three paediatric orthopaedic surgeons completed two rounds of a survey of anteroposterior and frog-leg lateral radiographs of patients with a diagnosis of SCFE (25), femoroacetabular impingement (four), Legg-Calvé-Perthes (11) or no hip pathology (ten). Intra- and interobserver agreement among specialties regarding the diagnosis of a SCFE were assessed using Cohen's kappa coefficient (κ). Diagnostic accuracy of SCFE relative to the benchmark, a combination of the radiographic diagnosis based on Klein's line, clinical symptoms and surgical treatment, was assessed computing sensitivity, specificity and accuracy. Results: Intraobserver agreement between the surveys was moderate among paediatricians (κ-range, 0.44 to 0.52), moderate to almost perfect among orthopaedic surgeons (κ-range, 0.79 to 0.88) and almost perfect among paediatric radiologists (κ-range, 0.83 to 1.00). Interobserver agreement for survey 1 and 2 was slight among paediatricians (mean κ, 0.19), substantial among orthopaedic surgeons (mean κ, 0.77) and almost perfect among paediatric radiologists (mean κ, 0.86). Sensitivity of SCFE-diagnosis was high among radiologists and orthopaedic surgeons (88% to 100% for both specialties), but lower for paediatricians (24% to 76%). Specificity was high among radiologists and orthopaedic surgeons (72% to 84%), however, variable among paediatricians (56% to 80%). Accuracy of a SCFE-diagnosis was highest in radiologists (84% to 92%), followed by orthopaedic surgeons (80% to 88%) and paediatricians (48% to 78%). Conclusion: SCFE can be detected on radiographs by different medical specialties. Intra- and interobserver agreement, specificity, sensitivity and accuracy for radiographic SCFE-diagnosis amongst paediatric radiologists and orthopaedic surgeons are better than that of general paediatricians. Level of Evidence: II